Modal Shift in the Context of Sustainable Development: A Bibliometric Exploration of Scientific Trends : Modal Shift in the Context of Sustainable Development: A Bibliometric Exploration of Scientific Trends - ACHRIH Lamia; TACHFINE Youssef (African Scientific Journal, 2025)
Abstract This article presents a bibliometric analysis of the scientific literature on modal shift within the framework of sustainable development, covering the period from 2015 to 2025. Modal shift referring to the transition from private motorized transport modes to more sustainable alternatives such as public transit, walking, and cycling has become a central issue in strategies aimed at ecological transition and urban resilience. The study is based on a final sample of 119 peer-reviewed articles, selected from the Web of Science database using the PRISMA method. The data were analyzed with Biblioshiny, part of the Bibliometrix package in RStudio. The objective is to map scientific trends, identify the most influential authors, institutions, countries, and journals, and to explore the conceptual structure of the field. The results reveal a continuous increase in publication volume, with a notable peak in 2022. European countries particularly Germany, the United Kingdom, and Belgium stand out for their high research output, while China and the United States are showing growing engagement. At the institutional level, universities such as Vrije Universiteit Brussel and TU Berlin emerge as key knowledge hubs. The keyword co-occurrence analysis highlights several thematic clusters focused on sustainable mobility, user behavior, emission reduction, and public policy. Modal shift is positioned as a pivotal concept that links these various research areas. The article concludes by advocating for stronger international collaboration and the integration of qualitative and interdisciplinary approaches to enrich the understanding of territorial and behavioral dynamics related to sustainable mobility. Keywords: Modal shift; Sustainable mobility; Bibliometric analysis; Urban transport